Dampak Sektor Pariwisata Terhadap Pertumbuhan Ekonomi di Kabupaten Banyuwangi - Mukaffi, Zaim; Tri Haryanto (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to determine the impact of the tourism sector (number of tourists, number of hotels, number of restaurants, number of tourist objects and purchasing power per capita) on PDRB of Banyuwangi Regency. This study uses secondary data for 2010-2020 obtained from the Central Statistics Agency (BPS) Banyuwangi Regency. Data analysis using multiple linear regression method where the model is transformed into the natural logarithm of the econometric model. From the partial test, it is found that there are four variables that affect the PDRB of Banyuwangi district, namely the number of tourists (X1), the number of restaurants (X3), the number of tourist objects (X4) and per capita purchasing power (X5). While the variable number of hotels (X2) has no effect on the PDRB of Banyuwangi Regency. While the simultaneous test showed that together the number of tourists (X1), the number of hotels (X2), the number of restaurants (X3), the number of tourist objects (X4) and Per capita Purchasing Power (X5) had a  ositive and significant effect on the PDRB of Banyuwangi Regency.